Negative space in branding: حاتم كاطع لكن حسن العطواني (Al-Academy, 2021)
Human interest in negative space has existential roots, in addition to its cognitive value of things. In the environment, it includes space features from facts and activities, as negative space plays an active role in the field of visual perception, and this value comes from the need to absorb vital relationships in its environment, Man represents the positive part of negative space through his presence in this environment, and therefore this is reflected in the design of its types and the function of each element in the design, for the real effectiveness that the elements gain and their impact comes through the negative space that surrounds them and organizes their relationships with other elements, that the orientation is distributed according to the same The relationship, such as inside, outside, closest, and farthest, as well as the separated, united, continuous, and non-continuous, and its function and basic knowledge lies in its meanings and embodiment of structural elements, that the importance of constructive space, and its priorities follow design treatments, so the research problem manifested itself with the following question:)What is the role of negative space in branding?With the aim of the research specified in: (to identify the representation of negative space in the design of brands). The theoretical framework was concerned with four topics, the first topic touched on: (the concept of negative space in the design of the brand), while the second topic focused on: (the relationship of negative space with the structure), and the third topic touched on: (negative space in light of the Gestalt theory). The fourth research, B (Design of commercial negative space marks), then four research models were described and analyzed, based on the paragraphs of analysis drawn from the theoretical framework, and the resulting indicators. After that the researcher presented the results and the conclusions reached by the researcher, and from the results:- Bilingual slogans subscribed to the iconic, formal content of the emblem of the Kingdom of Saudi Arabia, (the two crossed swords are surmounted by a palm tree), as in all samples and at 100%, which in turn contributed to establishing the identity of the emblem and stability in the minds of the receiving audience. The researcher organized the recommendations that he explored in the light of the results of his research, including:- The need for Iraqi institutions and companies to pay attention to designing bilingual slogans and the slogan in particular to keep pace with the scientific development in the field of design, through the use of academic and specialized designers.Then the search was appended to the list of sources related to the research ... and the research summary is in English.